Robust optmized control of multi levels STATCOM - Tedjini Hamza; Messaoud Fatima Zahra; Kadri Boufeldja (Institute of Advanced Engineering and Science, 2019)
Reactive power compensation is an essential part of a power system and the static synchronous compensator (STATCOM) plays an important role in controlling the reactive power flow over the transmission line. The basic building block of the STATCOM is a voltage source inverter (VSI) that generates a synchronous sinusoidal voltage and because of the high MVA ratings, it would be expensive to provide independent, equal, regulated dc voltage sources to power the multilevel converters which are presently proposed for STATCOMs. Dc voltage sources can be derived from the dc link capacitances which are charged by the rectified ac power. In this paper a new stronger control combined of nonlinear control based Lyapunov’s theorem and Ant Colony Algorithm (ACA) to maintain stability of multilevel STATCOM and the utility.